Physical activity and recreational screen time among Chinese children and adolescents: a national cross-sectional study - Guo, Mingming; Zhu, Yangming; Wang, Xiaozan (Frontiers in Public Health, 2024)
Background The increasing prevalence of physical inactivity and prolonged Recreational Screen Time (RST) among children and adolescents is emerging as a significant public health concern. This study investigates the current status of Physical Activity (PA) and RST among Chinese children and adolescents from 2017 to 2019. It also examines variations in PA and RST across different school levels, genders, urban–rural areas, regions, and seasons. Methods A national cross-sectional survey, conducted in China from 2017 to 2019, included 53,101 children and adolescents from grades 4 to 12 (aged 10 to 18 years old). Data on PA and RST were collected via self-administered questionnaires. The study employed descriptive statistics, calculated weighted prevalence rates, and conducted differential analysis across diverse demographic groups. Results Between 2017 and 2019 in China, merely 28.73% of children and adolescents adhered to World Health Organization’s PA guidelines, while 76.09% met China’s RST guidelines. Notably, females, higher-grade students, rural residents, and children and adolescents from southern regions exhibited significantly lower levels of PA compared to their male, lower-grade, urban, and northern counterparts. Concurrently, RST was significantly higher among males, lower-grade students, rural residents, and those from northern regions. Seasonal variations were also observed, with lower PA and higher RST in autumn and winter as compared to spring. Conclusion The study reveals a concerning low level of PA among Chinese children and adolescents, with marked disparities in PA and RST across different groups. This underscores the need for targeted health promotion strategies to enhance PA and mitigate RST among various child and adolescent populations.